1994
DOI: 10.1021/bi00189a004
|View full text |Cite
|
Sign up to set email alerts
|

Serine 90 Is Required for Enzymic Activity by tRNA-Guanine Transglycosylase from Escherichia coli

Abstract: An Escherichia coli mutant described by Noguchi et al. [Noguchi, S., et al. (1982) J. Biol. Chem. 275, 6544-6550] contains tRNA lacking the hypermodified wobble nucleoside queuosine (Q) due to an inactive tRNA-guanine transglycosylase (TGT). TGT catalyzes the posttranscriptional base exchange of the Q precursor preQ1 with the genetically encoded guanine in tRNA(Asp,Asn,His,Tyr). The mutant tgt gene was cloned and sequenced; it contained a single point mutation resulting in the change of serine 90 to phenylalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 13 publications
3
31
1
Order By: Relevance
“…Recently, we have reported that Ser-90 of the E. coli Tgt enzyme is essential for efficient catalysis (27). Mutated Tgts from E. coli with Ser-903Phe or Ser903Ala are inactive, while the Tgt with Ser-903Cys shows a reduced activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that Ser-90 of the E. coli Tgt enzyme is essential for efficient catalysis (27). Mutated Tgts from E. coli with Ser-903Phe or Ser903Ala are inactive, while the Tgt with Ser-903Cys shows a reduced activity.…”
Section: Discussionmentioning
confidence: 99%
“…By gel filtration, the apparent molecular mass of Z. mobilis Tgt was determined to be 55 kDa, suggesting a monomeric form. In contrast, it is known by cross-linking experiments and native PAGE that E. coli Tgt forms a homotrimer (5,6,13,27). Therefore, we examined the native molecular mass of the E. coli enzyme by gel filtration.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Site-directed mutagenesis studies determined that the observed loss of activity was catalytically significant, and not merely the result of a conformational change brought about by the non-conservative mutation [23]. This finding implicated an important role for serine 90 in TGT catalysis.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 91%
“…The recombinant TGT from E. coli is a 43-kDa enzyme that exists as a homotrimer in solution but dissociates into a monomer upon tRNA binding [22,23]. It is unclear if the trimeric structure is realized in vivo; however, it has been reported that the highly homologous TGT from Z. mobilis (ca.…”
Section: Trna-guanine Transgylcosylasementioning
confidence: 99%